High Dose Lopinavir/Ritonavir Does Not Lead to Sufficient Plasma Levels to Inhibit SARS-CoV-2 in Hospitalized Patients With COVID-19 - Mario Karolyi; Sara Omid; Erich Pawelka; Bernd Jilma; Thomas Stimpfl; Christian Schoergenhofer; Hermann Laferl; Tamara Seitz; Marianna Traugott; Christoph Wenisch; Alexander Zoufaly (Frontiers Media S.A., 2021)
Background: Despite lopinavir/ritonavir (LPV/RTV) demonstrating in-vitro activity against SARS-CoV-2, large trials failed to show any net clinical benefit. Since SARS-CoV-2 has an EC50 of 16.4 μg/ml for LPV this could be due to inadequate dosing.Methods: COVID-19 positive patients admitted to the hospital who received high dose LPV/RTV were included. High dose (HD) LPV/RTV 200/50 mg was defined as four tablets bid as loading dose, then three tablets bid for up to 10 days. Trough plasma concentrations were measured after the loading dose and on day 5-7 in steady state (SS). Post loading dose (PLD) and SS plasma trough levels were compared with SS trough levels from COVID-19 patients who received normal dose (ND) LPV/RTV (2 tablets bid) at the beginning of the pandemic.Results: Fifty patients (30% female) with a median age of 59 years (interquartile range 49-70.25) received HD LPV/RTV. Median HD-PLD concentration was 24.9 μg/ml (IQR 15.8-30.3) and significantly higher than HD-SS (12.9 μg/ml, IQR 7.2-19.5, p < 0.001) and ND-SS (13.6 μg/ml, IQR 10.1-22.2, p = 0.013). HD-SS and ND-SS plasma levels did not differ significantly (p = 0.507). C-reactive-protein showed a positive correlation with HD-SS (Spearman correlation-coefficient rS = 0.42, p = 0.014) and ND-SS (rS = 0.81, p = 0.015) but not with HD-PLD (rS = 0.123, p = 0.43).Conclusion: HD-PLD plasma trough concentration was significantly higher than HD-SS and ND-SS concentration, but no difference was detected between HD-SS and ND-SS trough levels. Due to the high EC50 of SARS-CoV-2 and the fact that LPV/RTV is highly protein bound, it seems unlikely that LPV/RTV exhibits a relevant antiviral effect against SARS-CoV-2 in vivo.